FENOMENA OVERTOURISM DI KAWASAN GUNUNG FUJI DAN SEKITARNYA - Hauzan, Mohammad Rafif; Subagio, Didit Dwi (UI Scholars Hub, 2025)
The phenomenon of overtourism has worsened in recent years. Not only in America and countries across Europe, but this issue has also increasingly affected popular destinations in Japan, one of which is Mount Fuji. The overtourism at Mount Fuji is driven by its designation as a UNESCO World Cultural Heritage Site and the availability of well-developed transportation facilities. Based on this context, this study discusses both the positive and negative impacts caused by overtourism in and around Mount Fuji, as well as the policies and solutions implemented by the government to address the issue. This research uses a qualitative method with a descriptive approach. The findings indicate that overtourism has had impacts in the areas of economy, environment, personal safety, and socio-cultural aspects.